Cote d’Ivoire : From Success to Failure - A Story of Growth, Specialization, and the Terms of Trade - Bogetic, Zeljko; Noer, John; Espina, Carlos (World Bank, Washington, DC, 2012)
Real GDP per capita and capital stock in Cote d'Ivoire grew strongly from 1960 to 1979, but have declined ever since, for twenty-five years. As a result, the country has traveled a full circle from economic success to failure in little more than a generation. What are the long-term factors behind this dismal growth story? Are the Ivorian development problems mostly of recent origin? Or there are more fundamental, economic factors that explain its long term performance? Four principal conclusions are as follows: First, Cote d'Ivoire's long-term growth performance is not fully explained by temporary factors (e.g., CFA overvaluation or recent conflict). Longer term factors such as capital accumulation, productivity, and terms of trade are key to understanding the country's performance as is the policy of specialization in a single commodity--cocoa. Second, the long-term decline in per capita output started well before the currency overvaluation, and at a time of political stability, and is related to a major, secular deterioration in terms of trade that started after 1976. Third, total factor productivity estimates indicate that TFP per capita also grew until it hit a plateau in 1976-78, and then shrank thereafter, despite gains in human capital accumulation. Fourth, Cote d'Ivoire has pursued a policy of specialization in cocoa beans but this bet on a single commodity has ultimately failed. The strategy that brought prosperity during the 1970s resulted in a growth failure when cocoa prices began declining since 1976.